ANALISIS PERBEDAAN TINGKAT PENJUALAN PREMIUM DAN PERTAMAX SEBELUM DAN SESUDAH ADANYA PERTALITE PADA PT PERTAMINA (PERSERO) MARKETING OPERATION REGION VII SULAWESI - Renny Mointi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
Analysis of Differences in Premium and Pertamax Sales Rates before and after the existence of Pertalite at PT Pertamina / Persero Marketing Operation Region VII Sulawesi. This study aims to analyze the differences in the level of premium and first sales sales before and after the existence of pertalite at PT Pertamina / Persero marketing Region VII Sulawesi. The analytical method used in this research is the Wilcoxon Parametric Paired Sample T - Test and Non Parametic Test, with the help of SPSS version 21.0 and using quantitative descriptive explanations. The observation period conducted is September and October 2015 .. The results of this study prove that there are differences in the level of premiumu and pertamax sales before and after the existence of pertalite at Sulawesi's PT Pertamina / Persero Marketing Operation Region VII Sulawesi.